Preparation and Spectroscopic Characterization of Iron(III) Complexes of a Functionalized Crown Ether - A. Aubed , Raed (University of Thi-Qar Journal of Science, 2019)
This research includes the synthesis and characterization of Shiff's bases crown ethersprepared from condensation between cis-diaminodibenzo-18-crown-6 and benzaldehydesubstituted with some groups such as; 4-H , 4-CH2(CH2)6CH 3 , 4-Cl , 4-Br and 4-NO2 and their complexes with Fe(NOO.The study involved solubility, melting points and thermal stability, elemental analysis have been detected with spectral studies using 1 H-NMR, UV-Visible and IR-spectroscopy .Theyfound to be solid crystalline and appear to be salt Shiff's bases crown ethers formed by Iondipole interaction between the cation and thenegatively charged oxygen atoms symmetrically placedin the crown ether ring .The complexes were prepared with molar ratio1:1(ligand:metal salt) .they were found to have the general formula :- [Fe (L) (NO3)3.9HO].23)3.9H2